Universities and Regional Engagement : From the Exceptional to the Everyday. - Iakovleva, Tatiana. (Regions and Cities Series, 2022)
This book presents a reconceptualision of universities' role in regional engagement and proposes a roadmap for a renewed research agenda. Starting from the grassroots level of universities' "everyday" engagements, the book delves into the manifold ways in which university knowledge agents build connections with regional partners.